The acoustic power radiated by a circular membrane excited for vibration both by means of the edge and by external surface load - Szemela, K.; Jr., W.P. Rdzanek; Rdzanek, W. (Archives of Acoustics, 2005)
In this paper the acoustic power of the circular membrane, excited both by the edge and external exciting forces uniformly distributed over the whole surface, is examined. Some different amplitudes of exciting factors and some differences between the phases of excitations were considered. It has been assumed that the source of a sound is located in a flat, rigid and infinite baffle and is sourrounded by a lossless and homogeneous fluid medium. The vibrations are axisymmetric and time-harmonic. Employing the Cauchy's theorem of residues and asymptotic formulae for the Bessel functions, the asymptotes for active and reactive power consisting of elementary functions are obtained. The acoustic power radiated by the membrane was shown graphically in terms of the parameters describing both kinds of excitations. Key words: acoustic radiation power, vibrations of a spherical membrane, excitation produced by edge and surface loads, amplitude-phase effects.